Enhancement of reducing sugar production by A. niger USM AI1 on oil palm frond in tray system via solid state fermentation - Lim Sheh Hong; Darah Ibrahim; Ibrahim Che Omar (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
To obtain higher reducing sugar production via solid state fermentation (SSF), it is necessary to develop a stabile bioprocess system. In this study, optimized the physical parameter of SSF in a shallow aluminium tray (30 cm x 20 cm x 6 cm) was carried out  in order to maximize  reducing sugar production by A. niger USM AI1 using oil palm frond as a substrate.  Production of reducing sugars before optimization in tray system was 185.00 ± 2.85 mg / g substrate with the fungal growth of 2.32 mg ± 0.06 glucosamine / g substrate. However, after optimization of physical parameter (amount of substrate, inoculum size, temperature and moisture content in substrate) the maximum reducing sugar yield was achieved 251.13 ± 1.95 mg / g substrate with the fungus growth of 3.21 ± 0.10 mg glucosamine / g on the 4 days of cultivation period.  The results showed that the production of reducing sugar was increased by 35.7% compared to before optimization.   Thus, optimized the physical parameter of solid state fermentation in a tray system has succeeded in increasing the production of reducing sugars. To meet the increasing demands of reducing sugar from biomass, it is necessary to obtain the optimum condition in SSF process